Operating Profit, Capital Adequacy and Operational Costs on Operational Revenues: Case of Vilage-Owned Enterprises - Gede Putu Agus Jana Susila (Universitas Pendidikan Ganesha, 2022)
This study was intended to examine the impact of capital adequacy and operational costs on operational revenues (BOPO) on operating profit at the same time and to some degree. This study was classified as causal quantitative study. The subjects of this study consisted of Village-Owned Enterprises in Banjar Sub-District, which were registered at the Village and Community Empowerment Service, and the objects included capital adequacy, operational costs, operational revenues and operating profit. The samples that were involved in this study were determined by means of purposive sampling with a total sample of six BUMDes. Moreover, data were gathered by means of document recording, and were then analyzed by using multiple linear regression analysis. The results showed that (1) capital adequacy and operational costs on operational revenues provided a significant effect on operating profit (2) capital adequacy provided a negative and insignificant effect on operating profit (3) operational costs on operational revenues had a negative and significant effect on operating profit.